Endoscopic repair through the medial wall of maxillary sinus for blowout fracture of the inferior orbital wall: a case report - Ryohei Oya; Takashi Shikina; Yukinori Takenaka; Atsuhiko Uno; Arata Horii; Hidenori Inohara (Acta Oto-Laryngologica Case Reports, 2017)
Endoscopic medial maxillectomy (EMM) was originally developed for surgery of maxillary sinus disease. This surgery was recently modified to preserve the inferior turbinate (IT) and the nasolacrimal duct (ND) and is commonly referred to endoscopic modified medial maxillectomy (EMMM). Here we present a case of endoscopic repair for a blowout fracture of the inferior orbital wall via access through the medial wall of the maxillary sinus, thereby preserving IT and ND, similar to EMMM. Two months postoperatively, a diplopia field test, computed tomography, and endoscopic observation were performed. Good recovery of diplopia was obtained, and empty nose syndrome, epiphora, and cheek numbness were not observed. Those complications such as empty nose syndrome, epiphora and cheek numbness can be avoided by the approach presented in this report; therefore, the maxillary medial wall approach, like EMMM, could become a preferred surgical method for blowout fractures of the inferior orbital wall.